Electroencephalographic Patterns in Chronic Pain: A Systematic Review of the Literature. - Eulália Silva dos Santos Pinheiro; Fernanda Costa de Queirós; Pedro Montoya; Cleber Luz Santos; Marion Alves do Nascimento; Clara Hikari Ito; Manuela Silva; David Barros Nunes Santos; Silvia Benevides; José Garcia Vivas Miranda; Katia Nunes Sá; Abrahão Fontes Baptista (PLoS ONE)
The main objective of this study is to review and summarize recent findings on electroencephalographic patterns in individuals with chronic pain. We also discuss recent advances in the use of quantitative Electroencephalography (qEEG) for the assessment of pathophysiology and biopsychosocial factors involved in its maintenance over time. Data collection took place from February 2014 to July 2015 in PubMed, SciELO and PEDro databases. Data from cross-sectional studies and longitudinal studies, as well as clinical trials involving chronic pain participants were incorporated into the final analysis. Our primary findings related to chronic pain were an increase of theta and alpha EEG power at rest, and a decrease in the amplitude of evoked potentials after sensory stimulation and cognitive tasks. This review suggests that qEEG could be considered as a simple and objective tool for the study of brain mechanisms involved in chronic pain, as well as for identifying the specific characteristics of chronic pain condition. In addition, results show that qEEG probably is a relevant outcome measure for assessing changes in therapeutic studies.